1982
DOI: 10.1159/000260623
|View full text |Cite
|
Sign up to set email alerts
|

Production of Acids in Rat Dental Plaque with or without Streptococcus mutans

Abstract: Little information is available on the production of acids in dental plaque of known microbial composition. In the present experiment monocarboxylic and lactic acids were assayed in rat dental plaque before and after exposure to sucrose. Actinomyces viscosus Nyl and Streptococcus sanguis Ny101 were the major organisms in the plaque in two groups of rats. Streptococcus mutans T2 was inoculated in one group of the rats where it accounted for 20% of the total viable counts. Organic acids in the plaque were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…These observations were consistent with the observed mixed-acid fermentation by streptococci in the dental plaque of gnotobiotic rats [2]. This indicated that, except during food intake by the host [3], the streptococci in dental plaque are under carbon and energy limitation and compete for these substrates [4]. At present it is not known how competition for carbon and energy sources would influence the proportions of these microorganisms in dental plaque, mainly because of the complexity of the natural ecosystem and because the available carbon and energy sources have not been studied in detail.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…These observations were consistent with the observed mixed-acid fermentation by streptococci in the dental plaque of gnotobiotic rats [2]. This indicated that, except during food intake by the host [3], the streptococci in dental plaque are under carbon and energy limitation and compete for these substrates [4]. At present it is not known how competition for carbon and energy sources would influence the proportions of these microorganisms in dental plaque, mainly because of the complexity of the natural ecosystem and because the available carbon and energy sources have not been studied in detail.…”
Section: Introductionsupporting
confidence: 89%
“…2 Substrates were selected for this experiment, sucrose and arginine. Both substrates are rapidly fermented in dental plaque [3,7,8] and can easily be supplied via the host's diet and drinking water. Several Streptococcus species can ferment arginine via ornithine to citrulline and carbamylphosphate [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An important feature is that calculations of the rates of growth of plaque organisms indicate that they grow at rates much slower than can be achieved under normal batch growth conditions (17) but which can be attained in the chemostat. The range of pH values examined, 5.5 to 7.5, is also relevant to oral ecology, and growth with limiting carbohydrate is pertinent because evidence indicates that plaque organisms are generally limited in their growth rate by the availability of carbohydrate (16,56).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical analysis. Organic acids in the suspended plaques were analyzed by isotachophoresis as described before (18,19). The isotachophoretic analysis has the advantage that no pretreatment of the samples was required, causing no loss of material from the small samples.…”
Section: Methodsmentioning
confidence: 99%